Genetic Diversity and Population Structure Reveal Cryptic Genetic Variation and Long Distance Migration of Puccinia graminis f. sp. tritici in the Indian Subcontinent - Prasad, Pramod; Thakur, Rajni Kant; Savadi, Siddanna; Bhardwaj, Subhash Chander; Gangwar, Om Prakash; Lata, Charu; Adhikari, Sneha; Kumar, Subodh (Frontiers in Microbiology, 2022)
Stem rust caused by Puccinia graminis f. sp. tritici (Pgt) is a devastating disease of wheat worldwide since time immemorial. Several wheat stem rust outbreaks have been reported worldwide including India. Approximately 7 mha wheat area in central and peninsular India is highly vulnerable to stem rust epidemics. In this study, a repository of 29 single genotype uredospore pathotypes, representing five geographical regions, was characterized by investigating their virulence phenotype and simple sequence repeat (SSR) genotypes using 37 reproducible polymorphic SSR markers, 32 of which had ≥ 0.50 polymorphic information content (PIC) value. Virulence phenotypes were used to evaluate the virulence frequency (VF) and construct a hypothetical evolutionary hierarchy of these pathotypes. We projected seven lineages to explain the evolutionary pattern of the Pgt population. The VF of these pathotypes ranged between 0% and 100%. The virulence-based neighbor-joining (NJ) cluster analysis grouped Pgt pathotypes into five virulence groups. Likewise, five molecular groups were categorized using molecular genotypes. The molecular grouping was supported by principal coordinate analysis (PCoA), which revealed 25% of the cumulative variance contributed by the first two axes. Analysis of molecular variance (AMOVA) revealed 8 and 92% of the variation among and within the populations, respectively. The Mantel test confirmed a positive but weak correlation (R2 = 0.15) between virulence phenotypes and SSR genotypes. The highest and lowest values of different genetic diversity parameters (Na, Ne, I, He, uHe, and %P) revealed maximum and minimum variability in the Pgt population from Maharashtra and Uttar Pradesh, respectively. The population structure analysis clustered 29 Pgt pathotypes into two subpopulations and an admixture. Our results demonstrated that there was significant genetic diversity among Pgt pathotypes resulting from their long-distance dispersal ability complemented by gene flow. These findings provide insights into the virulence patterns, genetic variations, and possible evolution of Pgt pathotypes, which would support strategic stem rust resistance breeding.